Ideologi Penggunaan Ketupat Krosok dalam Upacara Yadnya Umat Hindu (Studi Di Desa Bengkel Kecamatan Kediri Kabupaten Tabanan) - I Made Girinata (Jayapangus Press, 2020)
Ketupat has an important function and meaning for the life of the Hindu community, especially in Bengkel Village, Kediri District, Tabanan Regency both in social and ritual aspects. The connotation of the diamond for the community for the means of the ceremony is the matting of coconut leaves which is filled with rice and then boiled until cooked like rice. But Bengkel Village, Kediri Subdistrict, Tabanan Regency also uses krosok ketupat for its yadnya ceremony, which is ketupat which contains half-cooked and dry rice. This research uses a qualitative approach, which is sourced from primary and secondary data. Collected with techniques: observation, interview, and document study. The use of krosok ketupat for the community in Bengkel Village, Kediri Subdistrict, Tabanan Regency is based on the existence of ideology as the principle of understanding the modernity of the community which is implemented through applying but not deviating from the teachings of Hinduism. The reason why the ketupat ketupat was used in the Yadnya ceremony was because of practical and economic considerations, buying cheaper than the process of making it, and was easily available at any time. The religious implications of using ketupat krosok for the people of Bengkel Village, Kediri District, Tabanan Regency, that the community's confidence in carrying out the ceremony of Yadnya did not recede and instead became more enthusiastic. The economic implication is that people who carry out their yad ceremonies are economically able to carry out their obligations to work with income that is more profitable than setting aside special time to make a diamond by leaving time to work. While the ideological implications, that the Bengkel Village community, Kediri Subdistrict, Tabanan Regency, in the era of globalization in carrying out religious ceremonial obligations show the existence of a simplicative idea of ​​the use of diamonds. The use of ketupat in some forms of banten is simplified to become ketapap krosok, especially in banten when it is finished not to be diluted / thrown.